Role of proteases in oral carcinogenesis: Insights into the cancer degradome and therapeutic implications - Gargi S. Sarode; Sachin C. Sarode; Urmi Ghone; Rahul Anand (Oral Oncology Reports)
Cancer, a major global health concern, claims millions of lives annually, with oral squamous cell carcinoma (OSCC) representing a significant burden. Despite therapeutic advancements, OSCC's morbidity and mortality rates have seen little improvement over decades, necessitating deeper molecular understanding for effective treatment strategies. Proteases, essential enzymes regulating crucial cellular processes, emerge as promising targets and diagnostic markers in OSCC. OSCC's intricate pathogenesis involves dysregulation of proteolytic systems, prominently featuring cysteine proteases like cathepsins B and D, serine proteases including trypsin, and matrix metalloproteases (MMPs) such as MMP-9. These proteases drive tumor invasion, angiogenesis, and metastasis by degrading extracellular matrix components and modulating signaling pathways. Moreover, OSCC progression is exacerbated by the loss of protease inhibitors, notably membrane-bound serine protease inhibitor HAI-1. Understanding these proteolytic networks in OSCC offers insights into disease mechanisms and therapeutic avenues. Targeting specific proteases or their inhibitors holds promise for personalized OSCC treatment strategies. Further research into protease involvement in OSCC pathogenesis is warranted to enhance diagnosis, prognosis, and therapeutic outcomes, ultimately alleviating the burden of this devastating disease.